YOUNG LEARNERS’ ENGAGEMENT IN VOCABULARY LEARNING TAUGHT BY GAMES AND LEARNING APPLICATION: SYSTEMATIC REVIEW - Firliantama, Mochamad Rifki; Rokhayani, Atik (Universitas Muria Kudus, 2023)
Since the start of the twenty-first century, we have had access to a wide variety of new learning tools, including computers, mobile apps, and web-based resources that are used in English language classrooms. By that statement education need to adapt the technology by using it to make the student and teacher learning classes more effective. By that issue this research paper will be explaining what is the overall effect of the games and learning application across studies and what are the benefit from conducting their research. The findings from this research shown across different games and it can increase the student’s overall vocabulary score and activity in the classes in comparison when they are not using game to teach vocabulary. This article also provides information about the benefit of games to the student’s vocabulary skill. In conclusion from different cases of studies, all of the research proves that using games can increase vocabulary mastery.